2009
DOI: 10.1590/s0004-282x2009000500021
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant HMSN with proximal involvement: new Brazilian cases

Abstract: -We report four Brazilian siblings with Autosomal Dominant Hereditary Motor Sensory Neuropathy with Proximal Dominant Involvement (HMSN-P), a rare form of HMSN, that was characterized by proximal dominant muscle weakness and atrophy onset after the age of 30 years, fasciculation, arreflexia and sensory disturbances with autosomal dominant inheritance. Electrophysiological study and sural nerve biopsy were in the accordance with axonal sensory motor polyneuropathy and laboratorial analysis disclosed serum lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…Although the TFG was first reported to be a fusion partner of the NTRK1 gene, 13 the RNA-seq data revealed no TFG fusion with other genes, including NTRK. COMMENT In the literature, [6][7][8] HMSN-P has been described only in Japanese descendants; however, we could not find any record of a blood relationship between the present Korean family and the Japanese. Therefore, to our knowledge, this is the first report of a family with HMSN-P outside of Japan who are not Japanese descendants.…”
Section: Identification Of a P285l Mutation In Tfgcontrasting
confidence: 58%
See 1 more Smart Citation
“…Although the TFG was first reported to be a fusion partner of the NTRK1 gene, 13 the RNA-seq data revealed no TFG fusion with other genes, including NTRK. COMMENT In the literature, [6][7][8] HMSN-P has been described only in Japanese descendants; however, we could not find any record of a blood relationship between the present Korean family and the Japanese. Therefore, to our knowledge, this is the first report of a family with HMSN-P outside of Japan who are not Japanese descendants.…”
Section: Identification Of a P285l Mutation In Tfgcontrasting
confidence: 58%
“…6 Until now, HMSN-P has been reported only in Japan or in Japanese descendants. 7,8 Takashima et al 6 mapped the locus on chromosome 3q14.1-q13. Later, they suggested a narrowed locus on 3q13.1 within 3.1 cM.…”
Section: Conclusion and Relevancementioning
confidence: 99%
“…Its description emphasizes proximal dominant muscle weakness and atrophy, and also includes mild but obvious sensory dysfunction, fasciculation, decreased deep tendon reflexes, axonal degeneration in the peripheral nerves, and autosomal dominant inheritance. The disease appeared to be rare, and was originally reported only in patients of Japanese or Korean descent (Takashima et al, 1997;Takashima et al, 1999;Takahashi et al, 2007;Miura et al, 2008;Patroclo et al, 2009;Ishiura et al, 2012;Campellone, 2013;Lee et al, 2013). In 2015, we described a large Iranian HMSN-P affected pedigree and thus showed that the disease is not confined to individuals with Far East ancestry (Alavi et al, 2015).…”
Section: Introductionmentioning
confidence: 66%
“…A detailed comparison of phenotypic features of earlier described HMSN-P patients, all with the same p.Pro285Leu mutation in TFG, emphasized notable clinical variability within the framework of the original description of the disease (Takashima et al, 1997;Alavi et al, 2015 ). Some of the variable features were age at onset (from early 20's to late 60's), rate of disease progression, temporal order of upper and lower limb involvement, proximal only/ proximal and distal muscle weakness, and symmetric/ asymmetric onset (Maeda et al, 2007;Takahashi et al, 2007;Miura et al, 2008;Patroclo et al, 2009;Ishiura et al, 2012;Lee et al, 2013;Maeda, 2013;Alavi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Except for two recently described families from Iran, all reported HMSN‐P patients had Far East, usually Japanese, ancestry (Campellone, ; Ishiura et al, ; Lee et al, ; Miura et al, ; Patroclo, Lino, Marchiori, Brotto, & Hirata, ; Sarapura‐Castro et al, ; Takahashi et al, ; Takashima et al, ; Takashima et al, ). Clinical descriptions in the more recently diagnosed patients from Iran emphasized variability in presentations.…”
Section: Introductionmentioning
confidence: 99%